Issue Ownership and Agenda Setting in the 2019 Swiss National Elections. Issue 2 (23rd December 2021) - Gilardi, Fabrizio; Gessler, Theresa; Kubli, Maël; Müller, Stefan
Abstract: The 2019 Swiss national elections were characterized by the unusual prominence of two issues, environment and gender, whereas two staples of Swiss politics, immigration and Europe, were less dominant compared to previous elections. We study how, in this context, the media and party agenda were linked to issue ownership. Specifically, we consider whether political parties that own an issue could lead the media agenda and the agenda of other parties. Our analysis relies on all tweets and press releases of major Swiss political parties from January to October 2019 and 37, 225 newspaper articles published during the same period. Results show, first, that the agenda‐setting capacity of parties was restricted to the gender issue, and second, that the link between issue ownership and agenda setting is ambiguous. These findings suggest that during election campaigns, agenda setting may be largely exogenous to both parties and media. Zusammenfassung: Die Schweizer Nationalratswahlen 2019 waren durch die ungewöhnliche Bedeutung zweier Themen gekennzeichnet (Umwelt und Gleichstellung), während zwei Kernthemen der Schweizer Politik (Einwanderung und Europa) im Vergleich zu früheren Wahlen weniger im Fokus standen. Wir untersuchen, wie sich die Themensetzungen von Medien und Parteien gegenseitig beeinflusst haben. Konnten diejenigen politischen Parteien, die „issue owner" sind, die Agenden der Medien und der anderen Parteien beeinflussen? Unsere Analyse stützt sich auf alle Tweets und Pressemitteilungen der wichtigsten Schweizer Parteien von Januar bis Oktober 2019, sowie auf 37.225 Zeitungsartikel, die im selben Zeitraum zu den vier Themen veröffentlicht wurden. Die Ergebnisse zeigen erstens, dass sich die Agenda‐Setting‐Kapazität der Parteien auf das Thema der Gleichstellung beschränkt, und zweitens, dass der Zusammenhang zwischen „Issue Ownership" und Agenda‐Setting nicht eindeutig ist. Diese Ergebnisse weisen darauf hin, dass das Agenda‐Setting während des Wahlkampfs sowohl für die Parteien als auch für die Medien überwiegend exogen sein könnte. Résumé: Les élections nationales suisses de 2019 ont été caractérisées par la proéminence inhabituelle de deux enjeux, l'environnement et l'égalité des genres, alors que deux thèmes clés de la politique suisse, l'immigration et l'Europe, étaient moins dominants par rapport aux élections précédentes. Nous étudions comment, dans ce contexte, les agendas des médias et des partis étaient liés à la possession des enjeux. Notre analyse s'appuie sur les tweets et communiqués de presse des principaux partis politiques suisses de janvier à octobre 2019 et sur 37'225 articles de presse publiés au cours de la même période. Les résultats montrent que la capacité des partis à fixer l'agenda était limitée à l'enjeu de l'égalité des genres, et que le lien entre l'appropriation de la question et la fixation de l'agenda est ambigu. Ces résultats suggèrent que pendant les campagnes électorales, la fixation de l'agenda est largement exogène à la fois aux partis et aux médias.